Outside of Statistics, the Word "Regress" Means Going Backward. So Why Is Regression Such a Valued Statistical Tool?. Issue 9 (November 2015) - Unknown
Abstract : Regression models are commonly used in spine research today, and they can be used to explain or predict an outcome. A regression model can indicate the relative impact of each variable on the expected outcome, so when the model has been developed, it can be used to predict the outcome for a hypothetical patient.